2021
DOI: 10.3390/cells10123480
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Inhibits NLRP3 Inflammasome Activation in Obese Mice via the Anti-Inflammatory Effect of Meteorin-like

Abstract: Obesity is associated with chronic low-grade inflammation. The benefits of exercise are partly attributed to its anti-inflammatory effect, but whether exercise can regulate NLRP3 inflammasome activation in obese adipose tissue remains unknown. Meteorin-like (METRNL), a recently discovered myokine, has been implicated in mediating the effect of exercise on metabolism. Herein, we examined the effect of exercise and METRNL on NLRP3 inflammasome activation. High-fat diet (HFD)-induced obese mice were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Several recent studies have shown that physical exercise can inhibit NLRP3 upregulation in several experimental models [ 37 , 38 , 39 ]. Interestingly, we have previously shown that AT1 receptors and AT1-related inflammatory markers are upregulated in sedentary aged rats and can be decreased by physical exercise [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that physical exercise can inhibit NLRP3 upregulation in several experimental models [ 37 , 38 , 39 ]. Interestingly, we have previously shown that AT1 receptors and AT1-related inflammatory markers are upregulated in sedentary aged rats and can be decreased by physical exercise [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the in vitro effects of C. phaeocaulis translate into a decrease in IL-1β levels and inflammatory cell infiltration in an animal model of airway inflammation caused by nanoparticles. Considering the fact that NLRP3 inflammasome is mechanistically linked to diverse pathophysiological conditions, including insulin resistance and neuroinflammation [ 17 , 18 ], it will be scientifically worthwhile to evaluate C. phaeocaulis extract in other animal models of diseases associated with excessive activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it reduced the levels of gene and protein of inflammatory markers such as NLRP3 and caspase-1 in the adipose tissue. Also, in the isolated macrophages derived from bone marrow, it inhibited the activation of the NLRP3 inflammation pathway in the training group [ 31 ]. In another research, Sun et al conducted a study on JMT, as a combined traditional Chinese medication, which is being used for many to treat diabetic neuropathic pain and examined the effect of 12 weeks of JMT consumption on NLRP3 in the posterior region of the spinal cord of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%